2012
DOI: 10.1111/jbi.12041
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of tropical bird communities to tree species composition and vegetation structure along an Andean elevational gradient

Abstract: Aim Understanding patterns of species turnover along environmental gradients and their consistency across taxonomic groups is central to the study of biodiversity. We may expect congruence in diversity patterns across groups whose ranges could be influenced by species interactions. We explore associations between bird and vegetation communities in the tropical Andes to determine whether patterns of species richness and turnover in birds and trees are congruent with elevation, and whether tree species compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
183
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(200 citation statements)
references
References 59 publications
13
183
4
Order By: Relevance
“…Although there may be high species turnover rates in cloud forests (Jankowski et al 2013), we found an important variation in community composition for the largest fragment size category that was caused by changes in the abundance of forest understory and endemic species. Our results show that differences recorded in this study were mainly caused by the reduced numbers of forest-dependent understory insectivores in smaller forest fragments, possibly because of a greater influence of border effects (Banks-Leite et al 2010) and the associated structural changes in vegetation in smaller fragments that benefit the presence of omnivore species (Jankowski et al 2013). …”
Section: Discussionmentioning
confidence: 54%
“…Although there may be high species turnover rates in cloud forests (Jankowski et al 2013), we found an important variation in community composition for the largest fragment size category that was caused by changes in the abundance of forest understory and endemic species. Our results show that differences recorded in this study were mainly caused by the reduced numbers of forest-dependent understory insectivores in smaller forest fragments, possibly because of a greater influence of border effects (Banks-Leite et al 2010) and the associated structural changes in vegetation in smaller fragments that benefit the presence of omnivore species (Jankowski et al 2013). …”
Section: Discussionmentioning
confidence: 54%
“…Anand et al (2010) in their meta-analysis of 35 studies examining 14 taxonomic groups found that forest cover was a major influence on vertebrates in human-modified landscapes of the Ghats. Clough et al (2009) found that higher bird species richness in Indonesian cacao plantations was associated with tree density and Janowski et al (2012) found that tree species composition to influence bird species richness in the Andes. Bhagwat et al (2005) have demonstrated that tree cover may reduce the influence of patch area or isolation on species richness and have a buffering impact on biodiversity loss within human-cultivated landscapes in the Western Ghats.…”
Section: Discussionmentioning
confidence: 99%
“…This sets the background for further analyses of bird-habitat relationships at multiple spatial scales, particularly of species that are of ecological and conservation importance. Opportunities for future research include comparisons of multiple land uses with protected reserves, as well as examining spatial dynamics (such as local extinction, colonization, turnover and change in occupancy) over time (Janowski et al, 2012;Irizarry et al, 2016). This requires establishing long-term monitoring studies of bird communities in the region.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a distinct ecological transition occurs between 1500 and 1750 m. Recent publications from the Kosñipata elevation transect (including these two plots) present evidence of a step change in below-ground (Girardin et al 2013a) and above-ground (C. Girardin 2013, pers comm. ) productivity at the base of the cloud immersion zone, with significantly lower productivity rates and a sharp decline in tree biodiversity (Jankowski et al 2012) in plots located within the cloud immersion zone. As a probable increase in cloud immersion frequency at SPD 1750 is the main difference between the two sites, we conclude that the distinct ecological difference between these plots is likely to be related to the cloud immersion zone rather than the linear change in temperature with increasing elevation.…”
Section: Seasonal Trends and Climatic Drivers Of Npp And R A Componentsmentioning
confidence: 97%